Pengaruh Promosi Produk Dan Harga Terhadap Keputusan Pembelian Skincare Skintific Pada Mahasiswa Universitas 17 Agustus 1945 Surabaya - Sumar Liyana Warningrum (JURNAL RISET MANAJEMEN (JURMA), 2023)
This quantitative research is from a population with a total sample of 100 people. determination proves that product promotion has a partial effect on skintific skincare purchasing decisions, prices have a partial effect on skintific skincare purchasing decisions, from the calculation of simultaneous test statistics, it can be concluded that product promotion and price have a simultaneous effect on decisions on skintific skincare, by product promotion and price variables On the other hand, the deficiencies are described by variables that are not related to this study.